(untitled) (CIPEEX, 2025)
Introduction: Kidney transplantation is the most effective treatment for end-stage renal disease; however, the number of donor kidneys does not meet the high demand of patients with this condition. In this context, renal bioengineering is a potential therapeutic tool for obtaining functional kidneys for transplantation in patients with chronic end-stage renal disease. Methodology: This literature review focused on analyzing rat kidney decellularization methods in the preservation of the extracellular matrix (ECM). A bibliographic search was conducted in PubMed, Web of Science, and Scopus in September 2024 using the descriptors “extracellular matrix,” “decellularization,” “kidneys,” and “methods.” Results: Six selected articles were analyzed. The methods that used sodium dodecyl sulfate (SDS) and Triton X-100 were the most effective in preserving the extracellular matrix. Enhancement methods were also addressed, showing efficiency in practicality and speed. Conclusion: The most effective and most commonly used methods are those involving sodium dodecyl sulfate and Triton X-100, with emphasis on sodium dodecyl sulfate due to its practicality and results. Nevertheless, some limitations and challenges were recognized, including the absence of standardized renal decellularization protocols and the scale differences between rats and humans.